Wireless Energy Transmission Link Optimization considering Microwave Energy Relay - Yuanming Song; Yajie Liu; Xu Yang (Complexity)
With the widespread application of intelligent unmanned units and the development of wireless energy transmission technology, it has become an urgent requirement in the field of using wireless power transmission to extend the continuous working time of unmanned units. To improve the wireless transmission energy efficiency in practical application as much as possible based on the current development level of wireless transmission technology, this paper first enumerates and analyzes existing wireless energy supply methods and shows that microwave wireless energy transmission technology is most suitable in this study. Then, the necessity of power transmission relay in long-distance microwave wireless power transmission is discussed. Based on the idea of microwave energy relay transmission, the paper constructs a microwave wireless transmission link planning model which considers power relay and uses the evolutionary algorithm to solve the wireless transmission link planning model with two-layer optimization. Finally, the results show that, when the wireless transmission distance exceeds a certain threshold, adding relay nodes to the link can improve the energy transmission efficiency from the power supply node to the power receiving node.